On the trade-offs between hard and soft-skills skills: the Spanish case - Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro; Henriques, Carla Oliveira (My University, 2022)
The increasing relevance of non-cognitive skills (i.e., soft skills) for individual development and socioeconomic growth, and the well-established importance of cognitive skills in explaining socioeconomic success, highlights the need of exploring their main determinants (factors) and establishing to which extent there are potential trade-offs between different aspects of soft and hard skills. Towards this end, this study develops an overarching empirical framework, which couples multiobjective programming optimisation models with several econometric specifications, thus making it possible to gain further insights regarding the way these factors should be combined to achieve an “optimally balanced” performance of Andalusian students at nine cognitive and non-cognitive skills. Our findings underline the existence of several trade-offs between different soft and hard skills, being mainly conditioned by socioeconomic factors (e.g., household income, reading habits) and students’ gender.
Keywords: Aptitud; Desarrollo económico y social; ANDALUSIA; Hard skills; Soft skills; Multiple objective programming; Andalusia